Strategies to strengthen socially responsible public procurement practices in German municipalities: A mapping exercise - Maximilian Müngersdorff; Tim Stoffel (Deutsches Institut für Entwicklungspolitik (DIE), 2020)
Socially Responsible Public Procurement (SRPP) is a tool to use the market power of the public sector to trigger private companies to provide socially responsible products and services. In this sense, SRPP contributes to achieving SDG 12 of the Agenda 2030 ("Ensure sustainable consumption and production patterns"). However, while regulations at EU level and within the member states encourage SRPP, German municipalities lack effective implementation of social criteria in their tenders. This gap seriously decreases the triggering effect of the country's procurement expenditures of which municipalities account for more than 50 per cent. By triangulating interview data with secondary literature, this paper identifies success factors and triggers for the introduction and consolidation of SRPP practices in German municipalities. Our research shows that there is not one gold standard of implementing SRPP in a municipality (as suggested by most existing toolboxes and handbooks on the topic). Rather, our paper presents a compilation of various different entry points from which practitioners may embark on fitting pathways. Beyond this, we have translated the most crucial success factors and triggers into nine recommendations for political action, for example, with regard to clear and ambitious regulations; measures to ensure broad support for SRPP within the municipal administration; and approaches for a more strategic procurement management. Our research also highlights the role played by individuals, that is, the importance of personal commitment for successful implementation of SRPP. This finding, however, is problematic when it comes to transferring and upscaling good practices. To reach a high level of broad and ambitious SRPP action, the balance between individual, regulatory and institutional measures has to change for the benefit of the latter two.
Keywords: 330